Synthesis of Thiophosphates by Coupling of Phosphates with Bunte Salts under Mild Conditions - Min, Cong; Zhang, Rongxing; Liu, Qian; Lin, Sen; Yan, Zhaohua (Synlett, 2018)
A simple, green, and efficient method has been developed for the preparation of thiophosphates with sodium S-benzyl thiosulfates. The method uses an NaBr-catalyzed coupling reaction of Bunte salts with phosphonates in the presence of an acid and hydrogen peroxide (30%), and the desired products were obtained in good yields.
Keywords: hydrogen peroxide; thiophosphates; Bunte salts; synthesis; acids